The main events of the Russo-Japanese war in coverage «Frankfurter Zeitung» newspaper - V. S. Dzyuba; I. V. Makarov (Омский научный вестник: Серия "Общество. История. Современность")
The article examines the reaction of the regional German periodicals to the events and results of the Russian-Japanese war on the basis of the publications of one of the largest regional newspapers in Germany «Frankfurter Zeitung» (Frankfurt am Main, 1856–1943) from January to September 1905. The most significant attention is given to coverage of the surrender of Port Arthur, the battle of Mukden, the battle of Tsushima and the peace negotiations at Portsmouth, caused the most noticeable reaction and the activity of the newspaper and analytical articles in newspapers concerning the Russian-Japanese war. On the basis of these publications, the editorial policy of the newspaper related to the countries participating in the war and the direction in which the newspaper adjusted the regional public opinion of Germany in relation to these countries is analyzed